Rapid Response Team Activations in Oncologic Ambulatory Sites: Characteristics, Interventions, and Outcomes. Issue 12 (28th December 2022) - Majeed, Jibran; Chawla, Sanjay; Bondar, Ellen; Chimonas, Susan; Martin, Steven C.; O'Sullivan, Maryellen; Jones, Daryl
Abstract : PURPOSE: Patients with cancer are vulnerable to clinical deterioration. Rapid response teams (RRTs) identify and manage patients with acute changes in clinical status. Although RRTs have been well studied in the hospital setting, there are limited data on patients who require support in the ambulatory or outpatient oncologic settings. Describe baseline characteristics, reasons for activations, interventions, and outcomes of ambulatory oncologic patients receiving RRT activation in a tertiary cancer center. METHODS: We conducted a retrospective review of adult (age ≥ 18 years) patients requiring RRT activation at multiple ambulatory sites between July 2020 and June 2021. Demographic and clinical data captured include age, sex, race, ethnicity, do not resuscitate status, vital signs, receipt of active cancer treatment within 30 days, and cancer type. Using Kaplan-Meier survival analysis and multivariable Cox proportion hazard ratio regression models, outcomes of 90-day mortality and hospitalization were assessed. RESULTS: There were 322 RRT activations among 427, 734 visits to 10 ambulatory sites (0.75 RRTs/1, 000 visits). The most frequent reasons were syncope (25.2%), fall (24.5%), and adverse reaction to cancer therapy or intravenous contrast (16.5%). One hundred thirty-seven (42.5%) required transfer to an emergency department, of which 81 (59.1%) required hospital admission. At 90 days, 51 (15.8%) had died, with 44 (86.3%) receiving comfort measures. Kaplan-Meier survival analysis and multivariable Cox proportional hazard ratio regression showed that heart rate > 100 at RRT presentation and hospitalization after a RRT event were significantly associated with 90-day mortality. CONCLUSION: Although uncommon, patients with cancer undergoing care at ambulatory sites can suffer acute clinical deterioration needing RRT review. The rates of hospitalization and mortality among such patients are high, suggesting the need for improved end-of-life care.